2015
DOI: 10.1111/ppa.12411
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and structure of Hemileia vastatrix populations on Coffea spp.

Abstract: Coffee leaf rust is the most limiting disease for coffee cultivation in Brazil. Despite its importance, relatively little is known about the genetic diversity of Hemileia vastatrix, the rust causal agent. In this work, the DNA from 112 monopustule isolates from different geographic locations and coffee genotypes were analysed by amplified fragment length polymorphisms (AFLP). The objectives were to assess the influence of the host and geographic origin on the diversity and population differentiation in H. vast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 39 publications
2
42
2
4
Order By: Relevance
“…One of the first and most striking findings of this work was the discovery of three well‐diverged evolutionary lineages within our sampling of a supposedly single species, which is in disagreement with previous studies (Cabral et al ., ; Maia et al ., ; Rozo et al ., ). Until now, disease management practices were heavily influenced by the idea that Hv represents a large unstructured population that is able to freely switch between coffee species (McCook and Vandermeer, ; Zambolim, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the first and most striking findings of this work was the discovery of three well‐diverged evolutionary lineages within our sampling of a supposedly single species, which is in disagreement with previous studies (Cabral et al ., ; Maia et al ., ; Rozo et al ., ). Until now, disease management practices were heavily influenced by the idea that Hv represents a large unstructured population that is able to freely switch between coffee species (McCook and Vandermeer, ; Zambolim, ).…”
Section: Discussionmentioning
confidence: 99%
“…From the first epidemic report in Sri Lanka in 1869, Hv has spread to virtually every coffee-growing region in the world in about one and a half centuries (McCook and Vandermeer, 2015;Talhinhas et al, 2017). During this period, several major outbreaks have been registered in Asia and Africa and, more recently, since 2008, a cluster of outbreaks has been occurring across the Americas (Avelino et al, 2015;McCook and Vandermeer, 2015;Zambolim, 2016). Breeding for coffee resistance is considered to be the best long-term solution to control CLR (McCook and Vandermeer, 2015), but the introduction of resistant varieties in the field has inevitably resulted in the loss of resistance as a result of adaptation of the pathogen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are similar to those obtained in Brazil by Cabral et al (2016) Al no observarse en la red haplotípica de la Figura 2, nodos exclusivos por región geográfica, se estaría evidenciando una población de H. vastatrix grande e indiferenciada, que pudo haberse generado por el flujo de las esporas entre ambas zonas, favorecido por el movimiento de personas, semillas y/o plantas infectadas. Estos resultados son similares a los obtenidos por Cabral et al (2016) en Brasil, quienes no observan una estructuración de la población de H. vastatrix respecto a su origen, hospedero ni razas fisiológicas; sin embargo, la diversidad genética fue relativamente menor a la hallada en el presente trabajo. No obstante, Maia et al (2013) también en Brasil, obtuvieron resultados similares al presente trabajo, a través del estudio de 91 aislados del hongo, proponiendo que H. vastatrix se comporta como una gran población populations were structured based on their origin, host or physiological race.…”
Section: Resultados Y Discusiones Análisis De La Diversidad Genética unclassified
“…In another study, Maia, Maciel‐Zambolim, Caixeta, Mizubuti, and Zambolim () analysed the population structure of H. vastatrix from Brazil and observed high level of genotypic diversity using AFLP marker. In Brazil, Cabral, Zambolim, Oliveira, and Zambolim () studied the influence of host and geographic origin on the genetic diversity and population structure of H. vastatrix using AFLP markers and suggested that the fungal population revealed low levels of genotypic diversity. Recently, a new type of marker technology termed sequence‐related amplified polymorphism (SRAP) (Li & Quiros, ) was extensively used in the genetic diversity analysis of many fungal species such as Tricholoma matsutake (Ma, Yang, Mu, & Song, ), Puccinia striiformis (Pasquali, Komjati, Lee, & Bayles, ), Polyporous umbellatus (Zhang et al., ), Fusarium poae (Dinolfo, Castanares, & Stenglein, ) and Rhizoctonia solani (Tripathi & Dubey, ).…”
Section: Introductionmentioning
confidence: 99%